Pengaruh Kepemimpinan Kepala Sekolah dan Motivasi Kerja Guru terhadap Kompetensi Guru di SMP Negeri Se Kecamatan Prabumulih Barat - Nadia Farrah Soraiya; Alhadi Yan Putra; Syaiful Eddy (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
The purpose of this study is to analyze the influence of the principal's leadership and work motivation together on the competence of State Junior High School teachers in West Prabumulih District. This research was conducted at the State Junior High School, West Prabumulih District, Prabumulih City, for the 2023/2024 Academic Year. The research period was carried out for 3 months, namely January – March 2024. This study uses a quantitative method by analyzing the results of the research. The population in this study is 116 State Junior High School Teachers in West Prabumulih District, Prabumulih City. The sample in this study is 58 people. The data collection techniques in this study are questionnaires and documentation. The stage of implementing the analysis includes: (1) descriptive analysis, (2) analysis requirements test, and (3) hypothesis test. The results of the study were that there was a significant influence of the principal's leadership and teachers' work motivation simultaneously on the competence of State Junior High School teachers in West Prabumulih District. This means that the better the principal's leadership and teachers' work motivation, of course the teacher's competence will be better. Keywords: Leadership; Principal; Work Motivation; Teacher Competence